ANALYSIS OF THE EFFECT OF ALFAGIFT'S ELECTRONIC SERVICE QUALITY BASED ON OBJECTIVES USING THE E-SERVQUAL METHOD - Rafa Rizana Eka Putri; Marrylinteri Istoningtyas; Maria Rosario Boerroek (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
The times and technology are becoming retail business opportunities to compete online. This research was conducted with the aim to determine the effect of Alfagift service quality and the magnitude of the influence of e-servqual on user satisfaction Alfagift application. The study population was all people who had used the Alfagift application and the number was not known with certainty. So that the sample was taken using the non-probability sampling method type Purposive Sampling with the number of respondents taken as many as 130 respondents in the city of Jambi. The research data were processed using multiple linear regression methods through Statistical Product and Service Solution (SPSS) version 25. The results of data analysis showed the e-service quality hypothesis used in the study had a positive and significant effect on user satisfaction (0.878; t 10.991; sig 0.00).